Pengembangan Karakter Entrepreneur Siswa Melalui Pelatihan Kewirausahaan di SMK Inisial X di Gresik - Akhmad Wasiur Rizqi; Elly Ismiyah; Soffiana Agustin; Ahmad Fauzal Ibnu Amalik; M. Fauzan Eksando Pramaisyah (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Entrepreneurship training is an effective solution to foster and develop entrepreneurial character in students. This community service activity was implemented at Initial X Vocational High School in Gresik Regency, addressing the issue of students’ limited understanding of entrepreneurship principles and practices, despite some having experience assisting in family businesses. The primary objective of this program was to enhance students' motivation, broaden their entrepreneurial insights, and equip them with essential entrepreneurial skills through structured training sessions. The method of implementation included a combination of lectures, interactive discussions, question and answer sessions, hands-on practice, and intensive mentoring. The training process was divided into several stages: a pre-test to assess initial knowledge, delivery of materials, field practice to apply the concepts, and a post-test to measure the progress of the participants. The success of the program was measured by the level of participation from the partners, the activeness of the participants during the training, and the increase in knowledge and skills after the sessions. The results indicated a significant improvement in students’ understanding of entrepreneurial concepts, with a noticeable growth in their entrepreneurial character. Moreover, the students showed an increase in motivation to pursue entrepreneurship and were more confident in managing and designing businesses effectively. Through this training, students developed a better grasp of business principles and practices, which will help them become more independent and capable of running their own businesses. This community service initiative not only equipped students with valuable entrepreneurial knowledge but also laid the foundation for them to pursue entrepreneurial ventures in the future, contributing to the development of a more entrepreneurial mindset among the youth in the region.